2012
DOI: 10.5005/jp-journals-10015-1181
|View full text |Cite
|
Sign up to set email alerts
|

Elongated Styloid Process: A Retrospective Panoramic Radiographic Study

Abstract: The styloid process is a cylindrical, long cartilaginous bone which arises from the temporal bone in front of the stylomastoid foramen. In the present study, our aim is to investigate the number of asymptomatic styloid process elongation (SPE) in relation to gender, type of elongation and calcification pattern in patients visited to maxillofacial radiology department. We have investigated styloid process using panoramic radiographs taken of 517 patients referred to our hospital. A total of 80 patients (15.47%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
7
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
6
7
0
2
Order By: Relevance
“…In the present study, it was found that type I elongation was more common than other types of elongation on both right and left sides and the data were statistically significant; these observations were similar to the findings reported by few other studies 23,27,29…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, it was found that type I elongation was more common than other types of elongation on both right and left sides and the data were statistically significant; these observations were similar to the findings reported by few other studies 23,27,29…”
Section: Discussionsupporting
confidence: 93%
“…Most of the studies from different parts of the world have shown type 1 being the most common type of the styloid process, followed by type 2 and type 3 similar to our study [ Table 4]. [7,8,[10][11][12] Most of the studies have shown the type A as the most common pattern of calcification [7,10,11] [ Table 5]. In our study, type D was the most common pattern of calcification seen followed by type A.…”
Section: Discussionsupporting
confidence: 84%
“…These findings were in consistent with studies conducted by various authors. [1516] It was also observed that the styloid processes were elongated more in males when compared to females and more on the left side when compared to right side. However, these findings were not in consistent with studies conducted by various authors.…”
Section: Discussionmentioning
confidence: 95%